PRESERVING THE HAJAT SASIH TRADITION IN THE TRADITIONAL VILLAGE OF NAGA TASIKMALAYA - Linda Sari; Febi Dwi Fahriza; Mamat Supriatna (IKIP Siliwangi, 2026)
The Hajat Sasih tradition in Kampung Adat Naga, Tasikmalaya, is a series of annual ceremonies that reflect the harmony between Islamic teachings, Sundanese local wisdom, and ancestral cosmology. This study aims to describe the form, meaning, and socio-spiritual values of six rituals Muharaman, Rajaban, Ruwah, Nisfu Sya'ban, Idul Fitri, and Idul Adha while also examining customary prohibitions (pamali) as cultural preservation mechanisms. Using a qualitative ethnographic approach, data were collected through in-depth interviews with caretakers, traditional leaders, and residents, supported by documentation of sacred spaces, the forbidden forest, and ritual practices. The findings indicate that Hajat Sasih carries both spiritual and social functions: expressing gratitude, seeking protection, and strengthening communal cohesion. Customary prohibitions, such as avoiding stretching one’s legs toward the qibla, maintaining the leuweung larangan, and prohibiting photography of Bumi Ageng, serve to protect the sanctity of space and uphold adat values. These practices demonstrate how the community preserves cultural identity amid modern changes through rituals, taboo systems, and inherited knowledge. This research contributes to cultural anthropology and indigenous heritage studies, enriching discussions on the integration of religious and customary traditions in contemporary Sundanese society.